Reducing the allergenic capacity of β-lactoglobulin by covalent conjugation with dietary polyphenols. (1st August 2018) - Wu, Xuli; Lu, Yuqin; Xu, Haoxie; Lin, Dongxu; He, Zhendan; Wu, Haiqiang; Liu, Lizhong; Wang, Zimei
Highlights: The covalent interaction between the polyphenols and β-lactoglobulin was investigated. The allergenicity of β-lactoglobulin was reduced after covalent conjugation with polyphenols. The functional attributes of β-lactoglobulin were extended after covalent conjugation with polyphenols. Abstract: To help produce hypoallergenic food, this study investigated reducing the allergenicity and improving the functional properties of bovine β-lactoglobulin (βLG) by covalent conjugation with (−)-epigallo-catechin 3-gallate (EGCG) and chlorogenic acid (CA). The covalent bond between the polyphenols and the amino acid side-chains in βLG was confirmed by MALDI-TOF-MS and SDS-PAGE. Structural analysis by fluorescence spectroscopy, circular dichroism (CD) and Fourier transform infrared (FTIR) indicated that the covalent conjugate of EGCG and CA led to the changed protein structure of βLG. Western blot analysis and enzyme-linked immunosorbent assay indicated that conjugation of βLG with these polyphenols was effective in reducing the IgE-binding capacity of βLG. The conjugates maintained the retinol-binding activity without denaturation the protein and enhanced the thermal stability with high antioxidant activity. The study provides an innovative approach to producing hypoallergenic food.